17. yüzyılda yapılmış mensur şehname tercümesi : 261a-290b - Karayağız, Dilek (My University, 2006)
Üzerinde çalıstıgımız eser, stanbul Üniversitesi Merkez Kütüphanesi 6131 demirbas numarası ile kayıtlıdır. Üç cilt halinde ve tamamı 1778 varaktır. Ayrıca eserde minyatürlere yer verilmis, her sayfası 25 satır olarak düzenlenmistir. Üzerinde çalısılan 1. cildin boyu 39, eni 24.5 , kalınlıgı 7.5 cm ’dir. Eser Hicri 1187, Miladi 1773 yılında tamamlanmıstır. Kelime kelime bir tercüme degildir. Tez, yazmanın 261 a –290 b varaklarını kapsamaktadır. Bu tezi hazırlamaktaki amaç Sehnâme’nin bu mensur tercümesini tanıtmak ve 17. yüzyıla ait olan bu eser ile Eski Anadolu Türkçesinin dil özelliklerini görebilmektir. Bu çalısma giris, metin, ve sözlük olmak üzere üç bölümden olusmaktadır. Giris kısmında Firdevsi, Sehnâme, Sehnâme çevirileri ve üzerinde çalısılan yazma ile ilgili bilgiler verilmektedir. Metin kısmında sayfa ve satır numaraları belirtilmis, günümüz noktalama isaretlerine göre düzenlenmis ve gerekli kısımlarda paragraflar yapılmıstır. Böylece eserden faydalanılması daha kolay hale getirilmek istenmistir. Sözlük bölümünde eserin söz varlıgını gösteren bir indeks hazırlanmıs, eserdeki kelime ve birlesik sekillerin metindeki anlamları verilmeye çalısılmıstır. Madde bası veya ara maddelerin ikinci, üçüncü unsur olarak geçtigi maddelere (→) isareti ile göndermeler yapılmıstır.

The work of art we have been working on, is registered to the Central Library of stanbul University with the number 6131. It is composed of 3 volumes with total pages of 1778. Also miniatures have been taken place in the book with the pages designed in 25 lines. The length of the first volume on which the work is being carried on, is 39 cm, the width is 24.5 cm and thickness is based at 7.5 cm. The work was completed in 1187 – date based on Hegira, in 1773 – date based on Christian Era; The translation was not word for word. The thesis includes the pages 261a – 290 b of the manuscript. The goal of this thesis is to introduce the prose translation of Sehname and to examine the characteristics of the old Anatolian Turkish by the means of this work of art which belongs to the 17th century. In the introduction , information about Firdevsi, Sehname translations and manuscript on which the work is carried on, are given. In the text, the page and line numbers are shown, designed according to today’s punctuation marks and in necessary parts paragraphs are created. Therefore, it aimed at get benefit of the work more easily. In the dictionary, an index is prepared which shows the vocabulary of the book. The definitions of the words and compound forms in the book have been tried to be explained. The items identified as second and third factors of the main intermediary items, have been referred with the marking.
Keywords: İran Edebiyatı_Şehname; Türk Dili